The school environment and health education for confrontation to the COVID-19 - Yorka Robas-Valverde; Felipe Enio Robas-Díaz; Zulema de la Caridad Matos-Columbié (Revista Información Científica, 2022)
Introduction: at present, one of the world's problems it is the health situation. Cuba is not an exception, and the behavior of infestation due to the new outbreak of COVID-19 that is occurring at national level is a great concern.